A Sequential Approach to the Biodynamic Modeling of a Human Finger - Luka Knez; Janko Slavič; Miha Boltežar (Shock and Vibration)
In an effort to understand the vibration-induced injuries incurred by manual workers, mechanical models are developed and used to predict the biodynamic responses of human body parts that are exposed to vibration. Researchers have traditionally focused on the arms and hands, but there has been only limited research on finger modeling. To simulate the accurate response of a single finger, a detailed mechanical model based on biodynamic finger measurements is necessary. However, the development of such models may prove difficult using the traditional one-point coupling method; therefore, this study proposes a new approach. A novel device for single-finger measurements is presented and used to expose the finger to a single-axial broadband excitation. The sequentially measured responses of the different finger parts are then used to identify the parameters of a multibody mechanical model of the index finger. Very good agreement between the measured and the simulated data was achieved, and the study also confirmed that the obtained index-finger model is acceptable for further biodynamic studies.